2020
DOI: 10.1103/physrevmaterials.4.041002
|View full text |Cite
|
Sign up to set email alerts
|

Switchable two-dimensional electron gas based on ferroelectric Ca: SrTiO3

Abstract: Two-dimensional electron gases (2DEGs) can form at the surface of oxides and semiconductors or in carefully designed quantum wells and interfaces. Depending on the shape of the confining potential, 2DEGs may experience a finite electric field, which gives rise to relativistic effects such as the Rashba spinorbit coupling. Although the amplitude of this electric field can be modulated by an external gate voltage, which in turn tunes the 2DEG carrier density, sheet resistance and other related properties, this m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
(56 reference statements)
2
8
1
Order By: Relevance
“…The tunability of the 2DEG properties, their simple elaboration procedure and their efficient spin charge conversion capability not only make STO 2DEGs appealing for MESO-type devices but should also motivate experiments to probe further charge-spin conversion and spin-orbit torque. More generally, our results expand the research on STO 2DEGs for spintronics and open avenues towards the design of STO 2DEGs based on other reactive metals displaying functional properties [37][38][39].…”
Section: Discussionsupporting
confidence: 64%
“…The tunability of the 2DEG properties, their simple elaboration procedure and their efficient spin charge conversion capability not only make STO 2DEGs appealing for MESO-type devices but should also motivate experiments to probe further charge-spin conversion and spin-orbit torque. More generally, our results expand the research on STO 2DEGs for spintronics and open avenues towards the design of STO 2DEGs based on other reactive metals displaying functional properties [37][38][39].…”
Section: Discussionsupporting
confidence: 64%
“…PFM yields stable hysteresis loops at room temperature, as shown in Figure 6b, where low and high laser fluences during PLE clearly demonstrate their key role in creating FE polarization. Similar propositions were made by the Barthélémy-Bibes group, which invoked both an electric fieldswitchable two-dimensional electron gas emerging in ferroelectric SCT films [32] and the non-volatile electric control of spin-charge conversion in an STO Rashba system [33]. Only recently has another insight into the ferroelectric state of compressively strained STO become available from high-angle annular dark-field imaging in scanning transmission electron microscopy.…”
Section: Routes Of Srtio 3 Toward Ferroelectricity and Other Collective Statesmentioning
confidence: 62%
“…This assumption is supported by the observation of a large perpendicular polarization component in Al/Sr 1−x Ca x TiO 3 bilayers. [37] Our model comprises an electronic Hamiltonian, describing the 2DEG, and an ionic Hamiltonian, describing the lattice polarization. The lattice and electronic degrees of freedom are coupled through the self-consistently determined electric field.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Bréhin et al demonstrated that a switchable 2DEG forms in the perovskite layer of an Al/Sr 0.99 Ca 0.01 TiO 3 bilayer. [37] In both of these systems, the perovskite substrate is intrinsically insulating, and charge carriers are provided by the cap layer.…”
Section: Introductionmentioning
confidence: 99%